2014
DOI: 10.1080/15226514.2013.810574
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Riparian Wetland Plants to Perfluorooctanoic Acid (PFOA) Accumulation

Abstract: As plants have been shown to accumulate organic compounds from contaminated sediments, there is a potential for long-lasting ecological impact as a result of contaminant accumulation in riparian areas of wetlands, particularly the accumulation of non-biodegradable contaminants such as perfluorooctanoic acid (PFOA). In this study, commonly found riparian wetland plants including reeds, i.e., Xanthium strumarium, Phragmites australis, Schoenoplectus corymbosus, Ruppia maritime; Populus canescens, Polygonum salic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…There are various reports which have indicated the prevalence of PFASs (i.e., PFOA, PFOS, and PFBS) in several environmental matrices, including plants. For instance, Mudumbi et al [28] reported the susceptibility of riparian plants to PFOA accumulation in South Africa, Western Cape Province (WCP), while Krippner et al [35,36] indicated higher uptake of PFASs, including PFBS, into plant leaves. Recently, Kurwadkar et al [37], as well as Zhao and Zhu [38], addressed the uptake of PFASs in plants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are various reports which have indicated the prevalence of PFASs (i.e., PFOA, PFOS, and PFBS) in several environmental matrices, including plants. For instance, Mudumbi et al [28] reported the susceptibility of riparian plants to PFOA accumulation in South Africa, Western Cape Province (WCP), while Krippner et al [35,36] indicated higher uptake of PFASs, including PFBS, into plant leaves. Recently, Kurwadkar et al [37], as well as Zhao and Zhu [38], addressed the uptake of PFASs in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were pre-treated using protocols previously used by Tian et al [27] and Mudumbi et al [28], with minor changes. Thus, plant leaf samples ( n = 8) were harvested using a laboratory scalpel and oven-dried for 24 h at approximately 60 °C, and subsequently milled into a powder form.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations